The Role of Emerging Technologies of Students' Academic Achievement at Politeknik Seberang Perai (PSP) - Omar, Nurul Ihsaniah; Ibrahim, Mohammad Noor (UUM PRESS, 2024)
Education is crucial for global progress, constantly evolving with emerging technologies that impact teaching and learning. This essay explores how new technologies influence academic success, specifically examining elevated failure rates at Politeknik Seberang Perai (PSP) in Malaysia. Factors like insufficient information, slow progress, and inadequate time management are linked to these failure rates. The study investigates the influence of new technologies on academic achievement at PSP using an ex post facto research strategy and quantitative methods to collect data from 200 respondents across various departments. The research identifies the types of technologies used by students and evaluates their impact on academic performance. Chi-Square analysis and Spearman correlation coefficient are utilized to test hypotheses. Findings reveal that modern technology, particularly cell phones, is widely accessible to students, with notable discrepancies in access across departments. A weak correlation exists between the frequency of technology use and academic achievement, with a statistically significant association only found in obtaining material online. The study contributes to the literature on the use of new technologies for academic purposes within PSP. Results emphasize the necessity of educating students on effective technology use to enhance academic outcomes. It highlights that simply having access to new technologies does not guarantee academic success; it depends on how students integrate these tools into their learning processes. Recommendations include teaching students efficient technology utilization and recognizing that academic improvement is not assured solely by using technology. The study underscores the importance of strategic technology integration in education to foster academic achievement.